1983
DOI: 10.1002/ajmg.1320140116
|View full text |Cite
|
Sign up to set email alerts
|

A new short rib syndrome: Report of two cases

Abstract: We describe two unrelated malformed infants who died shortly after birth and who had multiple congenital anomalies including hydrops and ascites, facial abnormalities (with median cleft of the upper lip), narrow thorax, protuberant abdomen, and short, bowed limbs. Postmortem radiographs showed very short ribs and disproportionately short long tubular bones; no metaphyseal abnormalities were present. Comparison with earlier described short-rib/short-rib-polydactyly syndromes suggest that the disorder present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…For family 13, we were unable to screen DYNC2H1 due to insufficient amount of DNA and only NEK1 was excluded. The features of the five cases for which clinical details were available (table 1) were in agreement with previously reported SRP type IV cases,2 with the observation of various cerebral abnormalities (corpus callosum agenesis and cerebellar hypoplasia), intestinal malrotation, and heart defect.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For family 13, we were unable to screen DYNC2H1 due to insufficient amount of DNA and only NEK1 was excluded. The features of the five cases for which clinical details were available (table 1) were in agreement with previously reported SRP type IV cases,2 with the observation of various cerebral abnormalities (corpus callosum agenesis and cerebellar hypoplasia), intestinal malrotation, and heart defect.…”
Section: Resultssupporting
confidence: 87%
“…Other features include cleft lip/palate, malformed epiglottis and larynx, renal cysts, genital, cardiac, and intestinal abnormalities 1. It is closely related to Beemer-Langer syndrome or SRP type IV (MIM 269860) which is distinguished by inconstant post-axial polydactyly, short and often bowed long bones especially in the upper limbs, shorter fibula, and high frequency of brain defects 2. Recently, mutations in NEK1 have been identified in three families with SRP type II, and compound heterozygosity for mutations in NEK1 and DYNC2H1 were found in one family supporting a possible diallelic digenic inheritance 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In short rib polydactyly syndrome (SRPS) Majewski type, polydactyly has been a constant feature to date; therefore, no parentheses are used. The eponymic nomenclature of SR(P)S Beemer-Langer type is preferred in this article since Dr. Langer, a co-author of the original article, was instrumental in recognizing and delineating this condition as an entity [Beemer et al, 19831. Six patients with the characteristic radiographic combination of skeletal abnormalities of the Beemer-Langer type have been documented [Beemer et al, 1983 (2 cases); Wladimiroff et a]., 1981 (1 case); Garcia et al, 1988 (1 case); Winter, 1988 (1 case); Chen et al, 1989 (1 Fig. 6.…”
Section: Discussionmentioning
confidence: 96%
“…The SRPS types which overlap most are types 1 and 3 with similar clinical phenotypes. Type 3 is distinguished from type 1 by 50% male predominance, often no polydactyly, coarctation of the aorta, hypoplastic left and right side chambers of the heart, wide metaphyseal ends of the tubular bones, fan-shaped iliac bones and less severe radiologic manifestations [4,5,7,11,15,16] . Yang et al [17] reported that PAS-stained chondro-osseous cytoplasmic inclusions seen in type 3 were absent in type 1 SRPS.…”
Section: Discussionmentioning
confidence: 99%